2015
DOI: 10.1136/jech-2015-206012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reduced street lighting on road casualties and crime in England and Wales: controlled interrupted time series analysis

Abstract: BackgroundMany local authorities in England and Wales have reduced street lighting at night to save money and reduce carbon emissions. There is no evidence to date on whether these reductions impact on public health. We quantified the effect of 4 street lighting adaptation strategies (switch off, part-night lighting, dimming and white light) on casualties and crime in England and Wales.MethodsObservational study based on analysis of geographically coded police data on road traffic collisions and crime in 62 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(90 citation statements)
references
References 12 publications
1
80
1
Order By: Relevance
“…STATS19 provides routinely collected data about all RTAs in the UK which have resulted in a casualty and have been reported to the police 13. Detailed data are provided about each accident including date, casualty severity and location (precise coordinates).…”
Section: Methodsmentioning
confidence: 99%
“…STATS19 provides routinely collected data about all RTAs in the UK which have resulted in a casualty and have been reported to the police 13. Detailed data are provided about each accident including date, casualty severity and location (precise coordinates).…”
Section: Methodsmentioning
confidence: 99%
“…Steinbach et al examined the lighting practices of 62 local authorities in England and Wales, and found that part night lighting had little to no impact on rates of traffic accident or crime (in fact, there was weak evidence for decreases in crime in areas that switched lights off) [12]. Perhaps the lighting needs of smaller German communities could be met through a combination of reflective elements for traffic direction, and way-finding lighting for pedestrians.…”
Section: Discussionmentioning
confidence: 99%
“…The LANTERNS project [2] has its required protocol available on the website of its funder, the National Institute of Health Research, Public Health Research, See [20]. The full report of the project, Perkins et al [21], is available there for examination also.…”
Section: Publication Biasmentioning
confidence: 99%
“…My critical comments on the other hand said that nothing could be claimed because the review was inherently seriously flawed. Perhaps the points made there explain why the 'LANTERNS project' to determine the effect of reduced street lighting on road casualties and crime in England and Wales, found no detriment from implementing road lighting reductions despite involving a large dataset from 62 local authorities [2].…”
Section: Introductionmentioning
confidence: 99%